Analysis of Income Levels of Fish Processed Agroindustry in the Pondok Perasi Fishing Area, Ampenan District, Mataram City - Nur Ainisah; Hailuddin, Hailuddin; Suprianto, Suprianto (Tinta Emas Institute, 2023)
Indonesia is an archipelagic country with the second longest coastline in the world after Canada. Indonesia has a very high diversity of aquatic biological resources. One of them is marine fish resources with the potential for sustainable production reaching 6.4 million tons per year. This research aims to determine the production costs of processed fishermen's fish in Pondok Perasi, Ampenan District, Mataram City. To determine the income of the processed fishermen's fish agroindustry in Pondok Perasi, Ampenan District, Mataram City. The approach used by the author in this research is quantitative with descriptive methods. The data collection technique in this research is using questionnaires, literature study, description. The respondents used in this research were 12 respondents, of which 7 respondents processed processed Pindang Tongkol, 5 respondents processed processed Lanter Jerky. The results of the findings carried out by this research were that 600 cobs were processed multiplied by a selling price of IDR 6,000 per seed, resulting in an income of IDR 3,600,000. The total production costs incurred were IDR 3,770,000. The loss obtained in producing processed Tongol areca nut is IDR 170,000, while the processed 1,000 pieces of lanter jerked fish are multiplied by the selling price of IDR 1,000 per piece, the resulting income is IDR 1,000,000. The total production costs incurred were IDR 561,009,999. The profit obtained from producing processed lanter jerky fish is IDR 438,990.